Evidence reviews in energy and climate policy. (1st February 2020) - Warren, Peter
Abstract : Evidence reviews, commonly confused with literature reviews, are a crucial method not only for collating and synthesising the evidence base, but also for determining what the quality of previous evidence is and extracting the most amount of value from previous studies using systematic techniques. The paper focuses on the use of evidence reviews to inform the development of energy and climate policies, using the UK as a case study. A framework is proposed for understanding the different types of evidence reviews based on government resource constraints. Although the application of evidence reviews is growing, the method has received much less attention in the energy and climate policy field in comparison to other policy areas, such as health policy and social policy. This paper argues that the method (particularly systematic scoping reviews and Rapid Evidence Assessments) is resource-efficient, delivers good value-for-money and is comprehensive for informing the development of energy and climate policy within the timescales and resources of governments. They ensure that only high quality evidence is used (through the use of quality assessment scales), thus helping to ensure that policies maximise positive societal impacts, minimise any negative impacts, are defendable from an expert perspective, and that they learn from past experiences, both domestically and internationally. The paper discusses the practical challenges associated with the four main types of evidence review, and draws on the experiences of four evidence reviews commissioned in 2016‐2017 by the UK Government's Department for Business, Energy & Industrial Strategy (BEIS).